2019
DOI: 10.1073/pnas.1801480116
|View full text |Cite
|
Sign up to set email alerts
|

Clonal-level lineage commitment pathways of hematopoietic stem cells in vivo

Abstract: While the aggregate differentiation of the hematopoietic stem cell (HSC) population has been extensively studied, little is known about the lineage commitment process of individual HSC clones. Here, we provide lineage commitment maps of HSC clones under homeostasis and after perturbations of the endogenous hematopoietic system. Under homeostasis, all donor-derived HSC clones regenerate blood homogeneously throughout all measured stages and lineages of hematopoiesis. In contrast, after the hematopoietic system … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 58 publications
6
65
0
Order By: Relevance
“…2.2), near-complete engraftment with donor HbA was noted at 2 months, most likely related to clonal expansion of HbA HSCs. This is also consistent with some of our other studies and a recent report by Lu et al [29] where damage of the HSC niche by preconditioning with irradiation promoted clonal hematopoiesis. Secondarily transplanted animals were killed at 4 months, and donor HbA levels remained consistent (data not shown), confirming engraftment of long-term repopulating HSCs in the primary transplants.…”
Section: Nonmyeloablative Doses Of Treosulfan Permit Engraftment Of Lsupporting
confidence: 94%
See 1 more Smart Citation
“…2.2), near-complete engraftment with donor HbA was noted at 2 months, most likely related to clonal expansion of HbA HSCs. This is also consistent with some of our other studies and a recent report by Lu et al [29] where damage of the HSC niche by preconditioning with irradiation promoted clonal hematopoiesis. Secondarily transplanted animals were killed at 4 months, and donor HbA levels remained consistent (data not shown), confirming engraftment of long-term repopulating HSCs in the primary transplants.…”
Section: Nonmyeloablative Doses Of Treosulfan Permit Engraftment Of Lsupporting
confidence: 94%
“…A distinctly different electrophoretic band pattern in mouse 2.2 is due to clonally expanded HbA HSCs. A recent article by Lu et al [29] revealed that in mice some HSC clones become dominant because of preconditioning such as irradiation that are a consequence of stimulation or injury to the HSC niche. Finally, our data also support a threshold effect of nonmyeloablative treosulfan conditioning, and higher levels of erythroid chimerism are more likely to correct the hematologic abnormalities in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…These competitive BMT models serve to minimize the confounding effects that these driver gene mutations exert in animal models, including elevated immune cell levels and systemic tissue inflammation, which are generally not features observed in individuals with clonal hematopoiesis. Regardless, these experimental systems have significant drawbacks in modeling human clonal hematopoiesis because of the systemic effects of irradiation on cardiovascular tissues (18), damage to the bone marrow niche, (19) and lineage bias due to the differentiation of a small fraction of dominant HSC clones (20). In view of these issues, we investigated a model of murine clonal hematopoiesis that involves the adoptive transfer of unfractionated bone marrow cells to mice that have not been preconditioned by a myeloablative strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support the presence of pre-existing myeloid-biased LT-HSCs by demonstrating that myeloid-biased subpopulations of LT-HSCs in young, healthy mice respond to environmental challenges, such as inflammation and infection 18,19 . Results from lineage tracing with genetic barcodes 20,21 and single cell transplants of LT-HSCs also support the notion of inherent functional diversity among long-term repopulating HSCs 22-24 . However, these studies did not identify markers to prospectively isolate distinct sub-populations of HSCs.…”
Section: Introductionmentioning
confidence: 56%
“…Critically, our experimental results are based on the behavior of cells upon transplantation into young, irradiated mice. A recent study using individually barcoded HSCs showed that lineage biases are more pronounced after transplantation into lethally irradiated mice compared to unirradiated or anti-c-KIT-depleted syngeneic mice 20 . This suggests that post-transplant lineage bias may be either due to plasticity in lineage output or the selective engraftment of pre-existing HSC subsets.…”
Section: Discussionmentioning
confidence: 99%